High unacylated ghrelin levels support the concept of anorexia in infants with prader-willi syndrome. Issue 1 (December 2016) - Beauloye, Veronique; Diene, Gwenaelle; Kuppens, Renske; Zech, Francis; Winandy, Coralie; Molinas, Catherine; Faye, Sandy; Kieffer, Isabelle; Beckers, Dominique; Nergårdh, Ricard; Hauffa, Berthold; Derycke, Christine; et al.
Abstract Background Prader-Willi syndrome (PWS) is a rare genetic neurodevelopmental disorder with different nutritional phases from suckling deficit with failure to thrive to early onset of obesity. Hyperghrelinemia has been described in PWS long before the development of obesity. Ghrelin is found in both acylated (AG) and unacylated (UAG) forms in the circulation. In contrast to AG, UAG has been shown to inhibit food intake and to be elevated in anorexia nervosa. The present project is aiming to determine the underlying mechanisms driving the different nutritional phases in PWS. Methods Measurement of at least 4 h-fasting plasma acylated and unacylated ghrelin in 37 infants with a genetic diagnosis of PWS aged from 1 month to 4 years and in 100 age-matched controls without endocrine disorder recruited prior to minor surgery. One blood sampling was analysed for each patient/control and clinical data were recorded. Eleven PWS infants underwent repetitive blood samples at 3 or 6-month intervals during routine visits. Results In infants with PWS, AG is not elevated (p = 0.45), UAG is significantly higher (p = 0.0044; confidence interval 1.06;1.33) resulting in a low AG/UAG ratio (p = 0.0056; confidence interval 0.76;0.95) compared to controls. Conclusion Unlike children and adults with PWS that have high AG and AG/UAG ratio, infants with PWS have elevated UAG that supports the concept of anorexia in the early phases of the disease. The change in AG/UAG ratio possibly drives the switch from failure to thrive to obesity. Clinical trial registration NCT02529085 .